Monadic Curry System N-1* - Abe, Jair Minoro [UNESP]; Nakamatsu, Kazumi; Akama, Seiki; Setchi, R.; Jordanov, I; Howlett, R. J.; Jain, L. C. (Springer, 2010)
This paper is a sequel to [5], [6]. We present the Curry monadic system N-1* which has as extensions the Curry monadic algebras C-1* and P-1*. All those systems are extensions of the classical monadic algebras introduced by Halmos [13]. Also the Curry monadic system NI constitutes an algebraic version of the non-alethic predicate logic N-1*.
Keywords: Curry algebra; algebraic logic; paraconsistent logic; paracomplete logic; non-alethic logic